Nickel-manganese carbonate precursor material and method for producing same
Patent Information
- Application Number
- CN202580024422.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-03
- Filing Date
- 2025-04-03
- Publication Date
- 2026-11-03
AI Technical Summary
Existing positive electrode active materials for lithium-ion batteries exhibit poor stability at high operating potentials, and their preparation methods suffer from issues such as uneven particle size, low density, and high impurities, which affect the battery's energy density and cycle performance.
By using nickel-manganese carbonate precursor materials and controlling the molar ratio of Ni and Mn and the particle size distribution, a positive electrode active material with narrow particle size distribution, high density, and good sphericity was prepared. The transition metal ions were precipitated under neutral conditions using the carbonate co-precipitation method to avoid oxidation and phase separation.
It improves the electrochemical performance of the positive electrode active material, enhances the battery's discharge capacity and cycle stability, reduces irreversible capacity, and achieves higher energy density and packing density.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to the use of a nickel-manganese carbonate precursor material with a narrow span in the preparation of a positive electrode active material; to a positive electrode active material for a rechargeable battery; to a method for preparing the nickel-manganese carbonate precursor material and a method for preparing the positive electrode active material; and to a battery comprising the positive electrode active material. Background Technology
[0002] Energy storage systems such as rechargeable batteries are essential for rapidly storing and releasing large amounts of energy to regulate power output as needed. The same battery technology is used in electric vehicles, which operate on stored electrical energy and reduce pollution compared to conventional vehicles with internal combustion engines. To meet appropriate demands, these batteries need to store high levels of energy with minimal weight, charge and discharge at high rates, and withstand numerous cycles without performance degradation. These requirements are referred to as high energy density, rate performance, and cycle performance, and must be met while maintaining affordability and safety. Lithium-ion batteries (LIBs) have been extensively researched to meet these requirements, particularly due to their high energy density and rate performance. Lithium-ion rechargeable batteries are widely used in portable electronic devices such as mobile phones and laptop computers.
[0003] Lithium-rich and manganese-rich oxides have attracted significant attention due to their safety and energy density. However, these cathodes must be charged to above 4.5 V to achieve a high discharge capacity of approximately 250 mAh / g. This high operating potential (>4.5 V) severely impacts the long-term stability of these cathodes due to adverse reactions between the cathode and the electrolyte, as well as the dissolution of transition metals at the electrode-electrolyte interface. Consequently, the cycling performance of the cathode active material is reduced.
[0004] Lithium- and manganese-rich (LMR) layered oxides are promising cathode active materials for lithium-ion batteries due to their relatively low cost caused by low Co content. However, the cost of LMR layered oxides must be further reduced, and their energy density should be further improved.
[0005] Due to its multiple (and at least partially accessible) oxidation states, low toxicity, and high abundance, manganese is one of the most promising transition metals for use in battery materials. Mn-based cathode materials benefit from the advantages of Mn... 3+ / Mn 2+ or Mn 4+ / Mn 3+ Redox couples allow for potential ranges from 3.0 V to 4.2 V relative to Li+ / Li, depending on the crystal structure and chemical composition.
[0006] In current Li-ion battery materials, hydroxide coprecipitation is widely used to produce transition metal hydroxide precursors. However, this method has problems when preparing precursors with high manganese content because Mn... 2+ It is easily oxidized to Mn 3+ This process forms manganese hydroxide (MnOOH), causing the stoichiometry to deviate from the expected values. Furthermore, the resulting Mn-rich hydroxide precursors typically exhibit irregular morphologies and low packing density, resulting in low energy density and poor electrochemical performance of the cathode active material. Therefore, carbonate coprecipitation has emerged as an alternative method for preparing transition metal (Mn, Ni, Co) precursors. Its main advantage is that in the carbonate system, the oxidation state of all transition metal cations remains at 2+. Additionally, the experimental conditions for carbonate preparation are generally less stringent than those for hydroxide processes, i.e., the pH is typically closer to 8 than 11. However, carbonate precursors have some drawbacks, such as low tap density and high levels of impurities (Na, S).
[0007] EP2752923B1 discloses a positive electrode active material comprising a lithium metal composite oxide represented by the general formula: Li 1+u Ni x Co y Mn z M t O 2+α This invention relates to a method for the industrial production of non-aqueous secondary batteries, wherein the positive electrode active material has a uniform particle size distribution, which improves capacity and cycle characteristics when used in batteries, and also enables higher output. The patent discloses a Co-free Ni hydroxide precursor. 0.2 Mn 0.8 (OH)₂; and two Co-free cathode examples containing particles with a span of 0.46. [Comparative Example 1: Li] 1.3 Ni 0.2 Mn 0.8 O2 and comparative example 2: Li 1.6 Ni 0.2 Mn 0.8 [O2.]. However, it did not disclose a carbonate precursor.
[0008] US9643859B2 discloses a method for producing carbonate compounds and a method for producing positive electrode active materials. The patent discloses a cobalt-containing carbonate precursor [Ni...]. 0.4 Co 0.06 Mn 0.54 CO3 and Ni 0.39 Co 0.09 Mn 0.53CO3], having particles with a narrow span of 0.70; and a cobalt-containing cathode material comprising particles with a narrow span of [Li] 1.15 Ni 0.4 Co 0.06 Mn 0.54 O2 span = 0.86; Li 1.25 Ni 0.39 Co 0.09 Mn 0.53 O2 span = 0.68] Therefore, there is still a need for a Li-rich and Mn-rich cathode active material that is Co-free in order to prepare more cost-effective batteries, and also has higher capacity and lower irreversible capacity.
[0009] The purpose of this disclosure is to provide a precursor containing a transition metal that achieves improved stability and good electrode density characteristics, namely, optimal discharge capacity and irreversible capacity in lithium metal oxides.
[0010] Another object of this disclosure is to provide a method for preparing the precursor material.
[0011] Another object of this disclosure is to provide a method for preparing positive electrode active materials. Summary of the Invention
[0012] In a first aspect, the object of this disclosure is to provide a nickel-manganese carbonate precursor material for a positive electrode active material of a rechargeable battery, said nickel-manganese carbonate precursor material having a structure according to general formula (I) Ni x1 Mn y1 The composition of CO3, in which a. The molar ratio of Ni is x1, where 0.22 ≤ x1 < 0.50. b. The molar quantity of Mn is y1, of which 0.50 <y1≤ 0.78, The Ni and Mn contents, measured by ICP-OES, were x1+y1 = 1.00, and the particle size distribution of the precursor was characterized by (D 90 -D 10 ) / D 50 Less than 1.0.
[0013] Previously, the precursor had high density, regular particle size distribution (span), and high sphericity; the inclusion of particles with narrow span (≤1) enabled the positive electrode active material to have improved electrochemical performance, such as discharge capacity and irreversible capacity, as well as improved properties (easy to coat, low particle breakage rate, high DQ capacity and low Qirr).
[0014] In a second aspect, this disclosure provides a method for manufacturing a nickel-manganese carbonate precursor material, the method comprising the following steps: Step 1) Dissolve and mix NiSO4 and MnSO4 in water to obtain a first mixture; Step 2) Add an aqueous solution of Na2CO3 to the mixture to obtain a second mixture; Step 3) Stir the resulting second mixture at a temperature of 30°C to 90°C for at least 16 hours to obtain the third mixture; Step 4) Filter the third mixture to obtain a solid; Step 5) Heat the solid at a temperature of 80°C to 120°C for at least 10 hours to obtain the precursor material.
[0015] Specifically, in step 1), the concentration of the mixture can be about 100 g / L, and in step 2), the concentration of the Na2CO3 aqueous solution can be about 175 g / L.
[0016] In a preferred embodiment, the method further includes the step of sieving the product using a metal sieve with a mesh size between 130 µm and 170 µm.
[0017] In the third objective, this disclosure relates to the use of the nickel-manganese carbonate precursor material of this disclosure for the preparation of positive electrode active materials.
[0018] In a fourth aspect, this disclosure relates to a positive electrode active material obtained by using a nickel-manganese carbonate precursor material according to a first aspect of this disclosure, wherein the particle size distribution of the positive electrode active material is characterized in that (D90-D10) / D50 is less than 1.0.
[0019] According to this aspect of the disclosure, the positive electrode active material for a rechargeable battery comprises Li, M, and O, wherein M comprises: a. Ni with a molar ratio of x2, where 0.22 ≤ x2 < 0.50 relative to M; and b. Mn with a molar ratio of y2, where 0.50 is relative to M. <y2≤ 0.78; The molar ratio of Li to M is 1.0 to 1.6; the contents of Li, Ni and Mn are determined by ICP-OES, and x2+y2 is 1.00; and the particle size distribution of the positive electrode active material is characterized by (D90-D10) / D50 being less than 1.0.
[0020] In a fifth aspect, this disclosure provides a method for manufacturing a positive electrode active material according to a fourth aspect of this disclosure, the method comprising the following steps: Step 1) Provide a nickel-manganese carbonate precursor according to the first aspect of this disclosure; Step 2) The nickel-manganese carbonate precursor is mixed with a lithium source, wherein the lithium source content relative to the nickel-manganese carbonate precursor is 100 mol% to 160 mol% to provide a mixture; Step 3) Heat the mixture at a temperature of 800°C to 1100°C to prepare a heated product; Step 4) Grind the heated product to prepare a ground product, and Step 5) Optionally, the milled product is dried to obtain the positive electrode active material.
[0021] In a preferred embodiment, the method further includes the following steps: washing the positive electrode active material with water; and drying the positive electrode active material at a temperature of 80°C to 120°C.
[0022] In a sixth aspect, this disclosure provides a battery comprising a positive electrode active material according to a fourth aspect of this disclosure. Detailed Implementation
[0023] Preferred embodiments are described in detail in the following detailed description to enable the implementation of this disclosure. Although this disclosure has been described with reference to these specific preferred embodiments, it should be understood that this disclosure is not limited to these preferred embodiments. Rather, this disclosure includes many alternatives, modifications, and equivalents, as will become apparent from consideration of the following detailed description.
[0024] As used herein and in the claims, the term “comprising” should not be construed as limited to the elements listed thereafter; it does not exclude other elements or steps. It should be interpreted as specifying the presence of the features, integers, steps, or components mentioned, but does not exclude the presence or addition of one or more other features, integers, steps, or components, or groups thereof. Therefore, the scope of the expression “composition comprising components A and B” should not be limited to compositions consisting solely of components A and B. This means that, for the purposes of this disclosure, the only relevant components of the composition are A and B. Therefore, the terms “comprising” and “including” encompass the more restrictive terms “consistently composed of” and “composed of”.
[0025] As used herein and in the claims, the term "cathode active material" (also known as CAM or positive electrode active material) is defined as a material that is electrochemically active in a positive electrode or cathode. An active material must be understood as a material capable of capturing and releasing Li ions when subjected to a voltage change over a predetermined time period.
[0026] Within the framework of this disclosure, at% represents atomic percentage. The at% or "atomic percentage" expressed for a given element concentration indicates what percentage of all atoms in the compound are atoms of the element. The name at% is equivalent to mol% or "molar percentage".
[0027] As defined herein, the term "median particle size D50" (also known as volume median particle size Dv50) is used interchangeably with the terms "D50" or "d50" or "median particle size" or "median particle size (d50 or D50)". D50 is defined herein as the particle size at 50% of the cumulative volume percentage distribution. D50 is typically determined by laser diffraction particle size analysis. D10 and D90 (or Dv10 and Dv90) are defined, respectively, as the particle sizes at 10% and 90% of the cumulative volume percentage distribution when measured by laser scattering as described in this specification.
[0028] The term "about" refers to a measurable value such as a parameter, quantity, or duration, and is intended to cover variations that deviate from a specified value by + / -20% or less, preferably + / -10% or less, more preferably + / -5% or less, even more preferably + / -1% or less, and still more preferably + / -0.1% or less, provided that such variations are suitable for implementation in this disclosure. However, it should be understood that the value modified by the modifier "about" is itself specifically disclosed.
[0029] As used in this article, the value range "between X and Y" or "from X to Y" includes the endpoints X and Y.
[0030] As used in the text, the term “span” is defined as (D90 – D10) divided by D50; that is, (D90-D10) / D50. The term “narrow span” refers to a span of 1.0 or less.
[0031] A nickel-manganese carbonate precursor In a first aspect, the object of this disclosure is to provide a nickel-manganese carbonate precursor material for a positive electrode active material of a rechargeable battery, said nickel-manganese carbonate precursor material having a structure according to general formula (I) Ni x1 Mn y1The composition of CO3, in which a. The molar ratio of Ni is x1, where 0.22 ≤ x1 < 0.50. b. The molar ratio of Mn is y1, where 0.50 <y1≤ 0.78, Furthermore, the Ni and Mn contents (x1+y1) measured by ICP-OES were 1.00, and the particle size distribution of the precursor was characterized by (D... 90 -D 10 ) / D 50 Less than 1.0.
[0032] Preferred precursor materials have the general formula Ni 0.38 Mn 0.62 CO3, with a span of 0.44 to 0.57 and a D50 range of 13.5 µm to 7.75 µm.
[0033] The precursor material according to this first aspect of the disclosure may have one or more of the following characteristics: high density, regular particle size distribution (span), and high sphericity. Containing particles with a narrow span (<1.0) enables the cathode active material prepared using the precursor material according to the first aspect of the disclosure to exhibit improved electrochemical performance, particularly high discharge capacity and low irreversible capacity, and may also exhibit further improved properties such as ease of coating and low particle breakage rate.
[0034] In a preferred embodiment of the nickel-manganese carbonate precursor material, x1 is 0.25 ≤ x1 ≤ 0.45, preferably 0.30 ≤ x1 ≤ 0.40, more preferably 0.36 ≤ x1 ≤ 0.40, and most preferably x1 is 0.38.
[0035] In another preferred embodiment of the nickel-manganese carbonate precursor material, y1 is 0.55 ≤ y1 ≤ 0.75, preferably 0.60 ≤ y1 ≤ 0.70, more preferably 0.60 ≤ y1 ≤ 0.66, and most preferably y1 is 0.62.
[0036] In another preferred embodiment, the particle size distribution of the nickel-manganese carbonate precursor material is characterized by (D90-D10) / D50 being less than 0.8, more preferably less than 0.6, even more preferably less than 0.5, and most preferably less than 0.45.
[0037] In another embodiment, the median particle size D50 of the nickel-manganese carbonate precursor material, as determined by laser diffraction particle size analysis, is 1 µm to 14 µm, preferably 2 µm to 8 µm.
[0038] Nickel-manganese carbonate precursor materials are usually in powder form.
[0039] This aspect of the disclosure provides a Co-free precursor, thereby achieving the advantages of the disclosure, such as high density, regular particle size distribution (span), and high sphericity; comprising particles with a narrow span (<1.0).
[0040] A method for manufacturing nickel-manganese carbonate precursor materials In carbonate systems, transition metal ions (Ni, Co, and Mn) can precipitate completely above pH 7. In hydroxide systems, however, transition metal ions begin to precipitate at approximately pH 9.0. Compared to hydroxide systems, carbonates can precipitate under near-neutral conditions. Furthermore, MnCO3 is air-stable, and phase separation due to air oxidation of Mn(OH)2 during hydroxide precipitation is avoided in carbonate methods.
[0041] In a second aspect, this disclosure provides a method for manufacturing a nickel-manganese carbonate precursor material, the method comprising the following steps: Step 1) Dissolve and mix NiSO4 and MnSO4 in water to obtain a first mixture; Step 2) Add an aqueous solution of Na2CO3 to the first mixture to obtain a second mixture; Step 3) Stir the resulting second mixture at a temperature of 30°C to 90°C for at least 16 hours to obtain the third mixture; Step 4) Filter the third mixture to obtain a solid; Step 5) Heat the solid at a temperature of 80°C to 120°C for at least 10 hours to obtain the precursor material.
[0042] Specifically, in step 1), the concentration of the mixture can be about 100 g / L, and in step 2), the concentration of the Na2CO3 aqueous solution can be about 175 g / L.
[0043] In a preferred embodiment, the method further includes the step of sieving the product using a metal sieve with a mesh size between 130 µm and 170 µm.
[0044] In a third aspect, this disclosure discloses the use of the nickel-manganese carbonate precursor material for preparing positive electrode active materials.
[0045] The results show that when using the method for providing positive electrode active material according to the present disclosure, a precursor containing particles with a span <1.0 is converted into a positive electrode material containing particles with a span <1.0.
[0046] Positive electrode active material In a fourth aspect, this disclosure discloses a positive electrode active material obtained by using a nickel-manganese carbonate precursor material according to a first aspect of this disclosure, wherein the particle size distribution of the positive electrode active material is characterized in that (D90-D10) / D50 is less than 1.0.
[0047] The inventors have provided a positive electrode active material comprising particles with a narrow span. The narrow span of the positive electrode active material results in better safety and cycle stability, attributed to the uniform distribution of the positive electrode active material within the positive electrode. Furthermore, the narrow span allows for potentially higher energy density in the battery, as it enables the design of battery electrodes with higher volumetric packing density.
[0048] The median particle size D50 of this cathode material is 1 µm to 14 µm, as determined by laser diffraction particle size analysis. In a more preferred embodiment of the cathode active material, the D50 is 2 µm to 8 µm, and most preferably 2 µm to 4 µm.
[0049] In a preferred embodiment, the positive electrode active material comprises polycrystalline secondary particles. In a more preferred embodiment, the polycrystalline secondary particles are spherical. Such polycrystalline materials comprise a plurality of crystalline particles or primary particles bonded by grain boundaries. Thus, a secondary particle comprises two or more secondary particles. The number of primary particles constituting a secondary particle can be determined by counting the primary particles observed in a scanning electron microscope (SEM) image at a magnification of 2000 from a top view, where the overall shape of the secondary particle is obtained. In the context of this disclosure, primary particles can be distinguished in an SEM image by observing the grain boundaries between them. A grain boundary is defined as the interface between two primary particles, preferably wherein the atomic planes of the two primary particles are aligned in different orientations and intersect in a crystalline discontinuous manner.
[0050] According to this aspect of the disclosure, the positive electrode active material for a rechargeable battery comprises Li, M, and O, wherein M comprises: a. Ni with a molar ratio of x2, where 0.22 ≤ x2 < 0.50 relative to M; and b. Mn with a molar ratio of y2, where 0.50 is relative to M. <y2≤ 0.78; The molar ratio of Li to M is 1.0 to 1.6; the contents of Li, Ni and Mn are determined by ICP-OES, and x2+y2 is 1.00; and the particle size distribution of the positive electrode active material is characterized by (D90-D10) / D50 being less than 1.0.
[0051] In a preferred embodiment, the positive electrode active material has the formula Li w Ni x2 Mny2 O2, where: a. 1.00 ≤ w ≤ 1.60; b.0.22 ≤ x2<0.50; and c.0.50 <y2≤ 0.78; The contents of Li, Ni and Mn were measured by ICP-OES, and x2+y2 was 1.00; and the particle size distribution of the positive electrode active material was characterized by (D90-D10) / D50 being less than 1.0.
[0052] A preferred embodiment of the positive electrode active material has the general formula Li 1.0至1.6 Ni 0.38 Mn 0.62 O2, more preferably Li 1.2至1.3 Ni 0.38 Mn 0.62 O2, with a span of 0.45 to 0.63 and a D50 of 12.3 µm to 6.93 µm.
[0053] In a preferred embodiment of the positive electrode active material, x2 is 0.25 ≤ x2 ≤ 0.45, preferably 0.30 ≤ x2 ≤ 0.40, more preferably 0.36 ≤ x2 ≤ 0.40, and most preferably x2 is 0.38. In another preferred embodiment of the positive electrode active material, y2 is 0.55 ≤ y2 ≤ 0.75, preferably 0.60 ≤ y2 ≤ 0.70, more preferably 0.60 ≤ y2 ≤ 0.66, and most preferably y2 is 0.62.
[0054] According to this aspect, the particle size distribution of the positive electrode active material is characterized in that (D90-D10) / D50 is less than 1.0; preferably less than 0.8, more preferably less than 0.6, and most preferably less than 0.46.
[0055] Method for manufacturing positive electrode active materials The oxides disclosed herein can be prepared using a variety of methods, including but not limited to solid-state reaction, aqueous solution, or mechanochemical synthesis.
[0056] In a fifth aspect, this disclosure provides a method for manufacturing a positive electrode active material according to a fourth aspect of this disclosure, the method comprising the following steps: Step 1) Provide a nickel-manganese carbonate precursor according to the first aspect of this disclosure; Step 2) The nickel-manganese carbonate precursor is mixed with a lithium source, wherein the lithium source content relative to the nickel-manganese carbonate precursor is 100 mol% to 160 mol% to provide a mixture; Step 3) Heat the mixture at a temperature of 800°C to 1100°C to prepare a heated product; Step 4) Grind the heated product to prepare a ground product, and Step 5) Optionally, the milled product is dried to obtain the positive electrode active material.
[0057] In a preferred embodiment, the method further includes the following steps: washing the positive electrode active material with water; and drying the positive electrode active material at a temperature of 80°C to 120°C to obtain a washed and dried positive electrode active material.
[0058] In a preferred embodiment of this method, the grinding in step 4) is performed using a wet grinding process, such as wet bead (ball) grinding and wet ultrasonic treatment. As an alternative grinding technique, the method can use dry grinding, such as air jet grinding and air-stage grinding.
[0059] Batteries and their uses In a sixth aspect, this disclosure provides a battery comprising a positive electrode active material as described above according to the fourth aspect of this disclosure.
[0060] In a preferred embodiment, the battery is a lithium-ion battery, preferably a lithium-ion rechargeable battery. Preferably, the battery comprises a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the positive electrode comprises a positive electrode active material according to the fourth aspect of this disclosure. In a preferred embodiment, the battery may comprise a liquid electrolyte, such as a lithium salt in an organic solvent. Preferably, the battery further comprises a negative electrode, which comprises a negative electrode active material. Suitable electrochemically active negative electrode materials are those known in the art. For example, the negative electrode may comprise graphite carbon or a lithium-containing metal alloy. Preferably, the negative electrode comprises graphite carbon.
[0061] In a final aspect, this disclosure relates to the use of the battery according to the sixth aspect of this disclosure in any of portable computers, tablet computers, mobile phones, energy storage systems (ESS), electric vehicles (EVs), or hybrid electric vehicles (HEVs), preferably in electric vehicles or hybrid electric vehicles.
[0062] Examples and experimental tests The following description will be further detailed with reference to examples, but the disclosure is not limited in any respect to these examples, provided that they do not depart from the scope and spirit of the disclosure.
[0063] The following analysis methods were used in both instance and comparative instances.
[0064] Particle Size Distribution (PSD) Analysis - Data on particle size distribution (PSD), such as particle size at set percentiles (D10, D50, D90) and span, are preferably obtained by laser PSD measurement. PSD was measured using a Malvern Mastersizer 3000 with a Hydro 3000MV wet dispersion attachment. The sample was first dispersed in an aqueous medium for measurement. To improve the dispersibility of the powder in the aqueous medium, thorough ultrasonic irradiation and stirring were performed, and a suitable surfactant was added. It is important to note that a narrow span is an indicator of significant sphericity of the particles. D10, D50, and D90 are defined as the particle size at the 10%, 50%, and 90% cumulative volume percentage distribution, respectively. Span is defined as (D90 - D10) / D50.
[0065] Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) Analysis—The examples of positive electrode active materials and precursor materials described below were analyzed using an Agilent ICP 720-OES instrument. 1 g of powder sample was dissolved in 50 mL of high-purity hydrochloric acid in a conical flask. The flask was covered with a glass lid and heated on a hot plate to ensure complete dissolution. After cooling to room temperature, the solution was transferred to a thoroughly cleaned 500 mL volumetric flask rinsed with deionized (DI) water. After filling the flask with the solution, the volumetric flask was filled to the 500 mL mark with DI water and then completely homogenized. 5 mL of the solution was taken using a 5 mL pipette and transferred, along with an internal standard, to a 50 mL volumetric flask for a second dilution, in which the volumetric flask was filled to the 50 mL mark with 10% hydrochloric acid and then homogenized. Finally, this 50 mL solution was used for ICP measurements. The element content is expressed as at% of the total content of these elements.
[0066] The specific surface area of the positive electrode active material was determined using a Micromeritics Tristar II 3020 instrument via the Brunauer-Emmett-Teller (BET) method. Prior to measurement, the powder sample was heated at 150°C under nitrogen for 1 hour to remove adsorbed species. The dried powder was then loaded into a sample tube. The sample was then degassed at 30°C for 10 minutes. Nitrogen adsorption was tested at 77 K. The total specific surface area (in m² / g) of the sample was obtained by acquiring nitrogen isotherm adsorption / desorption curves.
[0067] XRD - XRD measurements were performed using a Rigaku D / MAX-2200 / PC X-ray diffractometer with Cu Ka. The scan rate was set to 1 degree per minute for continuous scanning. The step size was 0.02 degrees. Scans were performed between 15 and 85 degrees. Quantitative phase analysis was performed using TOPAS software.
[0068] Scanning Electron Microscopy – The morphology of the positive electrode active material was analyzed using scanning electron microscopy (SEM). The measurements were performed at 25°C under a high vacuum of 9.6 × 10⁻⁵ Pa using a JEOL JCM-6100 Plus. The particles in the image should be uniformly distributed to avoid overlap. This can be achieved by pouring a small amount of powder sample onto an adhesive attached to the SEM sample holder and blowing air to remove excess powder.
[0069] Button cell fabrication—To prepare the positive electrode, a slurry containing positive electrode active material powder, a conductor (Super P, Timcal), and a binder (KF#9700, Kureha) was prepared using a high-speed homogenizer in a weight ratio of 83:8.0:8.0 in a solvent (NMP, Mitsubishi). The homogenized slurry was spread onto one side of an aluminum foil using a doctor blade coater with a 230 μm gap. The slurry-coated foil was dried in an oven at 120°C and then pressed using a calender. It was then dried again in a vacuum oven to completely remove any remaining solvent from the electrode film. The button cell was assembled in an argon-filled glove box. A separator (Celgard 2320) was positioned between the positive electrode and a lithium foil used as the negative electrode. An EC / DMC solution containing 1 M LiPF6 (3:7 by volume) was used as the electrolyte and dropped between the separator and the electrode. The coin cell was then completely sealed to prevent electrolyte leakage.
[0070] DQ1, DQ8, and Qirr % schemes—using coin cell cells prepared according to the methods described above for discharge capacity (DQ) and irreversible capacity (Qirr %) testing.
[0071] The discharge capacity (DQ1) of the first cycle was measured at 25°C at a rate of 0.05C within the range of 4.8–2.0 V, where the 1C current in this application is defined using a capacity value of 160 mAh / g. The discharge capacity (DQ2) of the second cycle was measured at 25°C at a rate of 0.1C within the range of 4.6–2.0 V. The discharge capacity (DQ3) of the third cycle was measured at 25°C at a rate of 0.2C within the range of 4.6–2.0 V. The discharge capacity (DQ4) of the fourth cycle was measured at 25°C at a rate of 0.5C within the range of 4.6–2.0 V. The discharge capacity (DQ5) of the fifth cycle was measured at 25°C at a rate of 1C within the range of 4.6–2.0 V. The discharge capacity (DQ6) of the sixth cycle was measured at 25°C at a rate of 2C within the range of 4.6–2.0 V. The discharge capacity (DQ7) of the 7th cycle was measured at 25°C at a 3C rate within the range of 4.6–2.0 V. The discharge capacity (DQ8) of the 8th cycle was measured at 25°C at a 0.1C rate within the range of 4.6–2.0 V.
[0072] The irreversible capacity (Qirr) is defined by the following formula: , Where DQ1 is the discharge capacity of the first cycle and CQ1 is the charge capacity of the first cycle.
[0073] The DQ1' scheme—the scheme for measuring DQ1' refers to the scheme for measuring the initial discharge capacity fully described in EP2752923B1, page 28, paragraph 293. The initial discharge capacity is obtained as follows: after fabricating the coin cell, allow it to stand for approximately 24 hours, and after the OCV (open circuit voltage) has stabilized, set the current density at the positive electrode to 0.1 mA / cm². 2 Charge until the voltage reaches the cutoff voltage of 4.7 V, and then after resting for 1 hour, discharge until the voltage reaches the cutoff voltage of 2.5 V, and take the discharge capacity at this time as the initial discharge capacity.
[0074] According to the general scheme for synthesizing precursors in this disclosure: the precursors in this disclosure are obtained according to the precipitation process described below: a. NiSO4 and MnSO4 are dissolved in deionized water and mixed to obtain a first mixture with a concentration of 100 g / L. Then, an aqueous solution of Na2CO3 with a concentration of 175 g / L is added to the first mixture. The molar ratio between Na2CO3 and the metal sulfates (NiSO4 and MnSO4) is 0.9 to 1.1. The residence time, i.e., the duration for which the Na2CO3 solution is added to the first mixture, is at least 3 hours. The mixture is stirred at a temperature ranging from 45°C to 75°C for a duration ranging from 16 to 36 hours. The amounts of Na2CO3, NiSO4, and MnSO4 are adjusted to achieve the required stoichiometric ratio in the precursor materials.
[0075] b. Filter the resulting mixture through a Buchner filter (1 µm) and wash with water at 30°C to 80°C until the conductivity of the filtrate is less than 50 µS.
[0076] c. The washed and filtered solids are then dried in a Memmert furnace at 100°C and N2 at a heating rate of 5°C per minute for at least 10 hours. The resulting dried nickel-manganese carbonate is then sieved using a metal sieve with a mesh size of 150 µm and stored in aluminum bags.
[0077] d. Optionally, seed crystals can be generated by grinding the resulting nickel-manganese carbonate.
[0078] Synthesis of Example 1: Ni 0.29 Mn 0.71 CO3: Example 1 was synthesized according to the conditions described in the general scheme above.
[0079] Synthesis of Example 2: Ni 0.22 Mn 0.78 CO3: Example 2 was synthesized according to the conditions described in the general scheme above.
[0080] Synthesis of Example 3: Ni 0.23 Mn 0.77 CO3: Example 3 was synthesized according to the conditions described in the general scheme above.
[0081] Synthesis of Example 4: Ni 0.27 Mn 0.73 CO3: Example 4 was synthesized according to the conditions described in the general scheme above.
[0082] Synthesis of Example 5: Ni 0.36 Mn 0.64 CO3: Example 5 was synthesized according to the conditions described in the general scheme above.
[0083] Synthesis of Example 6: Ni 0.34 Mn 0.66CO3: Example 6 was synthesized according to the conditions described in the general scheme above.
[0084] Synthesis of Example 7: Ni 0.38 Mn 0.62 CO3: Example 7 was synthesized according to the conditions described in the general scheme above.
[0085] Synthesis of Example 8: Ni 0.38 Mn 0.62 CO3: Example 8 was synthesized according to the conditions described in the general scheme above.
[0086] Synthesis of Example 9: Ni 0.38 Mn 0.62 CO3: Example 9 was synthesized according to the conditions described in the general scheme above.
[0087] Seed crystal formation can be achieved by grinding precursor particles using Bühler Centex S2 and Tosoh YTZ 0.3 mm beads under the following conditions: a. Bead Level: 80% b. Tip velocity: 8.1 m / s c. Rotor speed: 2200 rpm d. Grinding type: number of passes e. Number of passes: 5 f. Product temperature during grinding: 28℃ Table 1. Summary of Na and S content, BET value, D90, D50, D10 and span of examples of carbonate precursors.
[0088] According to the general procedure for synthesizing the positive electrode active material disclosed herein: A mixture is prepared by mixing corresponding amounts of nickel manganese carbonate precursor and Li₂CO₃ in a Turbula mixer using 10 mm diameter zirconium oxide (ZrO₂) spheres for at least 2 hours. The mixture is then transferred to an alumina crucible and placed in a furnace with a dry air flow of 10 L / min. The furnace is subsequently heated from room temperature to 500 °C at 5 °C / min, and then to 925 °C at 1.5 °C / min. The furnace is held at 925 °C for at least 8 hours before cooling to room temperature at 5 °C / min. The resulting material is then transferred from the furnace to a drying chamber.
[0089] Synthesis of Example 11: Li 1.54 Ni 0.23 Mn 0.77 O2. Example 11 has been synthesized according to the conditions described in the general scheme above.
[0090] Synthesis of Example 12: Li1.49 Ni 0.27 Mn 0.73 O2. Example 12 has been synthesized according to the conditions described in the general scheme above.
[0091] Synthesis of Example 13: Li 1.34 Ni 0.36 Mn 0.64 O2. Example 13 has been synthesized according to the conditions described in the general scheme above.
[0092] Synthesis of Example 14: Li 1.29 Ni 0.34 Mn 0.66 O2. Example 14 has been synthesized according to the conditions described in the general scheme above.
[0093] Synthesis of Example 15: Li 1.28 Ni 0.38 Mn 0.62 O2. Example 14 has been synthesized according to the conditions described in the general scheme above.
[0094] Synthesis of Example 16: Li 1.27 Ni 0.38 Mn 0.62 O2. Example 16 has been synthesized according to the conditions described in the general scheme above.
[0095] Synthesis of Example 17: Li 1.23 Ni 0.38 Mn 0.62 O2. Example 17 has been synthesized according to the conditions described in the general scheme above. Synthesis of Example 18: Li 1.26 Ni 0.38 Mn 0.62 O2. Example 18 has been synthesized according to the conditions described in the general scheme above.
[0096] Synthesis of Example 19: Li 1.29 Ni 0.38 Mn 0.62 O2. Example 19 has been synthesized according to the conditions described in the general scheme above.
[0097] Example of a general solution: Synthesis of Example 20 – Li 1.28 Ni 0.38 Mn 0.62 O2. Using 10 mm diameter zirconia (ZrO2) spheres in a Turbula mixer, 25.0 g of Ni... 0.38 Mn 0.62The CO3 carbonate precursor was mixed with 10.9 g of Li2CO3 for 4 hours to prepare a mixture. Then, 25 g of the mixture was transferred to an alumina crucible and placed in a furnace with a dry air flow of 10 L / min. The furnace was heated from room temperature to 500 °C according to a temperature profile of 5 °C / min, and then to 925 °C at 1.5 °C / min. The furnace was held at 925 °C for 10 hours before cooling to room temperature at 5 °C / min. The final product was then transferred from the furnace to a drying chamber.
[0098] Synthesis of Example 21: Li 1.31 Ni 0.38 Mn 0.62 O2. Example 21 has been synthesized according to the conditions described in the general scheme above.
[0099] Comparative Examples 1 and 2: The synthesis of comparative examples 1 and 2 (CE1 and CE2 in Table 2) has been previously reported in EP2752923B1.
[0100] Table 2 - Summary of XRD data, BET values, D50, span, and electrochemical performance for example and comparative examples (CE)
[0101] As can be observed from the results shown in Table 2, Example 20 exhibits an improved discharge capacity (DQ1') compared to comparative Examples CE1 and CE2.
[0102] Furthermore, Examples 11 to 19 and 21 exhibit discharge capacities similar to those of Example 20, DQ1, ranging from 230 mAh / g to 260 mAh / g; and also have similar discharge capacities, DQ8, ranging from 216 mAh / g to 244 mAh / g.
Claims
1. A nickel-manganese carbonate precursor material for a positive electrode active material of a rechargeable battery, said nickel-manganese carbonate precursor material having a structure according to general formula (I) Ni x1 Mn y1 The composition of CO3, in which a) The molar ratio of Ni is x1, where 0.22 ≤ x1 < 0.50, b) The molar amount of Mn is y1, where 0.50 < y1 ≤ 0.78, where the sum of the contents of Ni and M, x1+y1, measured by ICP-OES is 1.00, and wherein the particle size distribution of the precursor is characterized in that (D90-D10) / D50 is less than 1.
0.
2. The nickel-manganese-containing carbonate precursor material according to claim 1, wherein 0.25 ≤ x1 ≤ 0.40, preferably 0.36 ≤ x1 ≤ 0.40, more preferably x1 is 0.
38.
3. The nickel-manganese-containing carbonate precursor material according to claim 1 or 2, wherein 0.55 ≤ y1 ≤ 0.75, preferably 0.60 ≤ y1 ≤ 0.66, more preferably y1 is 0.
62.
4. The nickel-manganese-containing carbonate precursor material according to any one of claims 1 to 3, wherein the particle size distribution of the precursor is characterized in that (D90-D10) / D50 is less than 0.6, preferably less than 0.
45.
5. A method for manufacturing the nickel-manganese-containing carbonate precursor material according to any one of claims 1 to 4, the method comprising the following steps: Step 1) Dissolving NiSO4 and MnSO4 in water and mixing to obtain a first mixture; Step 2) Adding an aqueous Na2CO3 solution to the first mixture to obtain a second mixture; Step 3) Stirring the resulting second mixture at a temperature of 30°C to 90°C for at least 16 hours to obtain a third mixture; Step 4) Filtering the third mixture to obtain a solid; Step 5) Heating the solid at a temperature of 80°C to 120°C for at least 10 hours to obtain the precursor material.
6. The method according to claim 5, further comprising the step of sieving the product with a metal sieve having a mesh size between 130 µm and 170 µm.
7. Use of the nickel-manganese-containing carbonate precursor material according to claims 1 to 4 for preparing a positive electrode active material.
8. A positive electrode active material for a rechargeable battery, the positive electrode active material comprising Li, M and O, wherein M comprises: Ni with a molar ratio of x2, where 0.22 ≤ x2 < 0.50 relative to M; and Mn with a molar ratio of y2, where 0.50 < y2 ≤ 0.78 relative to M; wherein the molar ratio of Li to M is 1.0 to 1.6; the contents of Li, Ni and Mn are measured by ICP-OES, and x2+y2 is 1.00; and wherein the particle size distribution of the positive electrode active material is characterized in that (D90-D10) / D50 is less than 1.
0.
9. A positive electrode active material obtained by using the nickel-manganese-containing carbonate precursor material according to claims 1 to 4, wherein the particle size distribution of the positive electrode active material is characterized in that (D90-D10) / D50 is less than 1.
0.
10. The positive electrode active material according to claim 8, having the formula Li w Ni x2 Mn y2 O2, in which ≤ w ≤ 1.60; ≤ x2<0.50; <y2 ≤ 0.78; and The contents of Li, Ni and Mn were measured by ICP-OES, and x2+y2 was 1.00; and the particle size distribution of the positive electrode active material was characterized by (D90-D10) / D50 being less than 1.
0.
11. The positive electrode active material according to claim 10, wherein 0.25 ≤ x2 ≤ 0.40, preferably 0.36 ≤ x2 ≤ 0.40, and more preferably x2 is 0.
38.
12. The positive electrode active material according to claim 10 or 11, wherein 0.55 ≤ y2 ≤ 0.75, preferably 0.60 ≤ y2 ≤ 0.66, and more preferably y2 is 0.
62.
13. The positive electrode active material according to any one of claims 8 to 12, wherein the particle size distribution is characterized in that (D90-D10) / D50 is less than 0.6, more preferably less than 0.
46.
14. A method for manufacturing a positive electrode active material according to any one of claims 8 to 13, the method comprising the following steps: Step 1) Provide a nickel-manganese carbonate precursor according to any one of claims 1 to 4; Step 2) The nickel-manganese carbonate precursor is mixed with a lithium source, wherein the lithium source content relative to the nickel-manganese carbonate precursor is 100 mol% to 160 mol% to provide a mixture; Step 3) Heat the mixture at a temperature of 800°C to 1100°C to prepare a heated product; Step 4) Grind the heated product to prepare a ground product; as well as Step 5) Optionally, the milled product is dried to obtain the positive electrode active material.
15. The method of claim 14, further comprising the steps of: washing the positive electrode active material with water; and drying the positive electrode active material at a temperature of 80°C to 120°C to obtain a washed and dried positive electrode active material.
16. A battery comprising a positive electrode active material according to any one of claims 8 to 13.
Citation Information
Patent Citations
Positive electrode active material for nonaqueous secondary batteries, method for producing same, and nonaqueous electrolyte secondary battery using positive electrode active material
EP2752923B1
Process for producing carbonate compound and cathode active material
US9643859B2
